Pengaruh Kinerja Keuangan dan Variabel Makroekonomi terhadap Nilai Perusahaan Sektor Barang Konsumsi di Bursa Efek Indonesia - Sembiring, Edy Suranta Karina (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
This study aims to (1) determine the effect of the financial performance of Return on Assets (ROA), Return on Equity (ROE), and Debt to Ratio (DER) on the value of the company projected through Price to Book Value (PBV) especially in the consumer goods industry; (2) identifying the effects of macroeconomic factors such as GDP, inflation, SBI, and the exchange rate on the value of companies in the consumer goods industry. The method used in this research is multiple linear regression analysis with panel data from 2014 to 2018. The results of this study indicate that: 1) Return on Asset (ROA) not significantly, Return on Equity (ROE), and Debt to Ratio variables (DER) significantly influence the value of shares (PBV). 2) Variable GDP, SBI Inflation and Exchange Rate significantly influence firm value (PBV). Companies in the Indonesian capital market especially in the consumer goods industry sector must more attention to their financial performance and macroeconomics condition because through the variables that have been tested in this study aimed a significant result on the value of the company.